Investigation of In Vitro Effects of Paracetamol on Bronchial Smooth Muscle Contraction in Female Rats - Pervin, Mehtap; Sayin, Orhan; Bozyil, Ahmed Sait; Oz, Zeynep Dila; Hekim, Munevver Gizem; Serhatlioglu, Ihsan; Kacar, Emine (Wiley, 2023)
[Abstract Not Available]
Keywords: Bronchus; Isolated organ; Paracetamol; Smooth muscle